Intelligent predictive control of coal moisture control system based on OSVR - MENG Yongzheng; LI Xiaobi (Gong-kuang zidonghua, 2016)
In view of problem of the long training time and mismatch model of existing coal moisture prediction model, a prediction model of coal moisture control based on OSVR was established, an intelligent predictive control method of coal moisture control system based on OSVR was proposed. The method adopts intelligent optimization algorithm and predictive functional control to realize accurate control of export coal moisture of coal moisture control system. The simulation and experimental results show that the proposed method has better robustness and higher control precision.